2006
DOI: 10.1271/bbb.60282
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Novel Nonmethylene-Interrupted C24Polyenoic Fatty Acids in Female Gonad Lipids of the LimpetCellana grata

Abstract: The occurrence of positional isomers of minor C 24 unsaturated fatty acids in female gonad lipids of the limpet Cellana grata was clarified by gas chromatography-mass spectrometry of the combination of their 4,4-dimethyloxazoline and picolinyl ester derivatives. In this study, in addition to 5,9-24:2, 9,15-24:2, 5,9,15-24:3, and 5,9,17-24:3, previously identified, 24:4n-6, 24:5n-3, and four novel nonmethylene-interrupted fatty acids, 9, 17-24:2, 9,15,18-24:3, 5,9,15,18-24:4, and 5,9,15,18,21-24:5, were newly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…6A). Twenty‐three structurally related fatty acid derivatives have been isolated from two of these species (Kawashima, 2005; Kawashima & Ohnishi, 2006), whilst the third species yielded a defensive terpene (Pawlik et al , 1986). Further research into the chemistry of this ancestral class of gastropods is justified, especially considering that limpets are only protected by a shell on their top surface and are found in very large numbers on most rocky intertidal shores.…”
Section: Taxonomic Distribution Of Molluscan Metabolitesmentioning
confidence: 99%
“…6A). Twenty‐three structurally related fatty acid derivatives have been isolated from two of these species (Kawashima, 2005; Kawashima & Ohnishi, 2006), whilst the third species yielded a defensive terpene (Pawlik et al , 1986). Further research into the chemistry of this ancestral class of gastropods is justified, especially considering that limpets are only protected by a shell on their top surface and are found in very large numbers on most rocky intertidal shores.…”
Section: Taxonomic Distribution Of Molluscan Metabolitesmentioning
confidence: 99%
“…Peaks were identified by their retention times, and mass spectra and FA compositions were calculated from the peak areas. [18][19][20] All data from GC analyses are presented as averages of at least three independent experiments, along with the standard deviations. …”
Section: Methodsmentioning
confidence: 99%
“…A scan range of 50-500 m/z was used. Most FA were identified by comparison of their mass spectra with those of authentic standards and published data [8,9,14]. In the absence of suitable standards, assignments were based on mass spectral fragments and on equivalent chain length (ECL) values for structurally analogous FA.…”
Section: Glc and Gc-ms Analysesmentioning
confidence: 99%
“…From the viewpoint of comparative biochemical interest, previous studies revealed that the significant differences between male and female gonads of two dominant limpet species, Cellana grata and Collisella dorsuosa, which are distributed in northern Japan, were characterized by their proportions of 16:0, 20:4n-6, and 20:5n-3 [7,8], and their composition and proportions of unusual nonmethyleneinterrupted (NMI) FA, whose physiological role and function are not fully understood. Furthermore, the positional isomers of unusual minor polyenoic FA with 24 carbon atoms have been also found in triacylglycerols (TAG) of the female gonads of C. grata, one of the commonest species, from the Sanriku coast, northern Japan [9]. Although mainly major FA and their characterization in limpet gonads have been investigated, the occurrence and unique structures of the unknown minor FA including NMI FA have yet not been well clarified.…”
Section: Introductionmentioning
confidence: 99%